Driving Climate Awareness through Knowledge and Action - Amyly, Yong Kai Hui; Vimala, Govindaraju (Gazette Unimas, 2025)
Final-year students from the Strategic Communication Programme, Faculty of Education, Language, and Communication (FELC), pulled off a successful roadshow as part of their PBK 4202, Strategic Campaign and Event Management course.